ROLE OF AYURVEDA IN THE MANAGEMENT OF OSTEOPOROSIS- A SHORT REVIEW - Jadhav, Dnyaneshwar Kantaram; Shaha, Gauravkumar V; Walale (Shaha), Chaitalee Anil; Bawiskar, Sankalpa s. (International Journal of Research -GRANTHAALAYAH, 2025)
Our advanced lifestyle gives luxury life to us. Fast food and fast life aggravate Vata dosha. This vata produced its own 80 types of diseases and other Awarana disease too. As Vata increases Asthi dhatu decreases. Decreased Asthi dhatu known as Asthi -kshaya.in modern, this can compare as osteoporosis. Osteoporosis means ‘poras bones’ when bone lose its minerals such as calcium than it becomes less dense, lose its strength and easily break. In early condition it’s not show any sign and symptoms and suddenly all symptoms occur. That’s why osteoporosis is called as silent disease.